De la célébration artistique au trouble émotionnel : les représentations discursives de Florence dans les récits des écrivains-voyageurs - Annick Farina (University of Tel-Aviv, 2021)
This study is based on a sub-corpus extracted from the French Corpus Lessico dei Beni Culturali (University of Florence), which contains travel writings of French-speaking authors ranging from the 16th to the 21th century, with Florence, the cradle of the Rinascimento, as a backdrop. We first analyze the various names that contribute to the discursive construction of this “mecca for tourists” (topographical names, chrononyms, titles of works). Secondly, we focus our attention on the stereotypical representations based on the value of “beauty” attributed to Florentine art works and monuments. Finally, we attempt to identify the discursive modalities that have the function of “desacralizing” these works, a desacralization that is strikingly expressed in the “Stendhal syndrome”, an emotional disorder with oxymoronic discursive characteristics (ethos and pathos)